2018
DOI: 10.1111/ele.13181
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants differentially affect soil biota through litter and rhizosphere pathways: a meta‐analysis

Abstract: Invasive plants affect soil biota through litter and rhizosphere inputs, but the direction and magnitude of these effects are variable. We conducted a meta‐analysis to examine the different effects of litter and rhizosphere of invasive plants on soil communities and nutrient cycling. Our results showed that invasive plants increased bacterial biomass by 16%, detritivore abundance by 119% and microbivore abundance by 89% through litter pathway. In the rhizosphere, invasive plants reduced bacterial biomass by 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
143
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(150 citation statements)
references
References 91 publications
(226 reference statements)
4
143
0
3
Order By: Relevance
“…This positive priming of soil microbial activity after extra energy inputs to soil has been widely reported (Kuzyakov 2010, Xiao et al 2015, and our analysis also found that invaded soils have significantly higher soil microbial biomass and basal respiration than noninvaded soils (Appendix S1: Fig. S5), suggesting higher activities of soil microbes after plant invasion (Zhang et al 2019). In specific examples, invasive plants have been shown to secrete root exudates actively that are rich in amino acids and proteins (Bais et al 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This positive priming of soil microbial activity after extra energy inputs to soil has been widely reported (Kuzyakov 2010, Xiao et al 2015, and our analysis also found that invaded soils have significantly higher soil microbial biomass and basal respiration than noninvaded soils (Appendix S1: Fig. S5), suggesting higher activities of soil microbes after plant invasion (Zhang et al 2019). In specific examples, invasive plants have been shown to secrete root exudates actively that are rich in amino acids and proteins (Bais et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…S5), suggesting higher activities of soil microbes after plant invasion (Zhang et al. ). In specific examples, invasive plants have been shown to secrete root exudates actively that are rich in amino acids and proteins (Bais et al.…”
Section: Discussionmentioning
confidence: 99%
“…Belowground organisms play important roles in regulating ecosystem functioning in terrestrial ecosystems (Bardgett & van der Putten, 2014; Zhang, Li, Wu, & Hu, 2019), mediating the cycling of carbon and other elements, and affecting aboveground community dynamics (Morriën et al, 2017). Compared with the well‐known geographic patterns in the diversity and abundance of aboveground organisms (Hillebrand, 2004; Mannion, Upchurch, Benson, & Goswami, 2014), the geographic patterns of belowground organisms are relatively understudied (but see Decaëns, 2010; Hendershot, Read, Henning, Sanders, & Classen, 2017; Maraun, Schatz, & Scheu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in plant species composition affect the quantity and quality of root exudates to the soil 1-3 alter rates of nutrient cycling [4][5][6] , and change inputs of organic matter to the soil 1 . Despite an increasing knowledge of how invasive plants change these soil properties, relatively little is known about how invasive plants influence soil microbial community structure and function 2,4,5,7,8 . Changes in the chemical and physical properties of soil, as well as in litter and exudate inputs, are almost certain to impact microbial community assembly processes and community composition, which in turn, will alter ecosystem services.…”
Section: Background and Summarymentioning
confidence: 99%